Current status of and factors influencing anxiety and depression in front‐line medical staff supporting Wuhan in containing the novel coronavirus pneumonia epidemic. Issue 2 (1st December 2020) - Li, Laiyou; Sun, Ning; Fei, Suding; Yu, Libo; Chen, Shuangqin; Yang, Shuang; Li, Hongyu
Abstract: Aim: This research aimed to shed light on the relationship between the sociodemographic characteristics of front‐line medical workers and their anxiety and depression, to provide the basis and reference for targeted mental health education and for relevant departments to formulate appropriate policies during the COVID‐19 outbreak. Methods: This study adopted a convenient sampling method and examined the psychological status of 150 front‐line medical workers from Zhejiang Province with questionnaire surveys using the Hamilton Anxiety and Depression Scale. Results: The participants had severe anxiety and depression; the top three items under the category of anxiety were genitourinary symptoms, behavior at interview, and respiratory symptoms, whereas the top three items under depression were feelings of guilt, weight loss, and retardation. Among all personal data, the following factors influenced anxiety, in decreasing order: degree of suspicion of being infected when showing associated symptoms, degree of fear of yourself and your family being infected, and the affiliated hospital ( p < .05). As for depression, the factors were the degree of suspicion of being infected when showing associated symptoms and the degree of fear of yourself and your family being infected ( p < .05). Conclusion: This study revealed that front‐line medical staff presented symptoms of anxiety and depression when dealing with the COVID‐19 outbreak and the factors influencing their psychological stress. Guiding policies and psychological interventions is crucial to maintaining their psychological well‐being. Different measures may be implemented to solve this problem.